Construcción de principios de realidad y producción de sentidos a partir de los realitys shows combate y calle 7 - Abril Estévez, Cristhian Javier (2018)
The present article is structured based on phenomenological and communicational principles. In this way, the reality shows “Combate” and “Calle 7” were subjected to a communicational analysis in order to later develop an audience study based on workshops with people from the municipality of Yaruqui. This made an investigation possible where the central fundamentals were the principles of reality and production of the senses that originated from these programs. In other words, the goal is to find results that don’t revolve around the logic of capital but rather give evidence for meaning that relates to ontological and phenomenological dimensions. The ontological dimension is the principle fountain through which the work can develop. In this way, as well as through a Heideggerian phenomenological method and communicational tools, the senses that originate in the spectator are shown. The average relationship of the subject is fundamental since from this the senses will be regulated between a margin of existential authenticity and inauthenticity.